Transcriptome Analysis of Eucalyptus grandis Implicates Brassinosteroid Signaling in Defense Against Myrtle Rust (Austropuccinia psidii) - Swanepoel, Shae; Oates, Caryn N.; Shuey, Louise S.; Pegg, Geoff S.; Naidoo, Sanushka (Frontiers in Forests and Global Change, 2021)
Eucalyptus grandis, in its native Australian range, varies in resistance to Austropuccinia psidii. The biotrophic rust fungus, A. psidii is the causal agent of myrtle rust and poses a serious threat to Australian biodiversity. The pathogen causes yellow pustules of urediniospores on growing leaves and shoots, resulting in shoot tip dieback, stunted growth, and seedling death. Dissecting the underlying mechanisms of resistance against this pathogen will contribute to improved breeding and control strategies to mitigate its devastating effects. The aim of this study was to determine the molecular dialogue between E. grandis and A. psidii, using an RNA-sequencing approach. Resistant and susceptible E. grandis seedlings grown from seed collected across their natural range were inoculated with the pandemic biotype of A. psidii. The leaf tissue was harvested at 12-hours post inoculation (hpi), 1-day post inoculation (dpi), 2-dpi and 5-dpi and subjected to RNA-sequencing using Illumina 50bp PE reads to a depth of 40 million reads per sample. Differential gene expression and gene ontology enrichment indicated that the resistant seedlings showed controlled, coordinated responses with a hypersensitive response, while the susceptible seedlings showed no systemic response against myrtle rust. Brassinosteroid signaling was apparent as an enriched term in the resistant interaction at 2-dpi, suggesting an important role of this phytohormone in defense against the pathogen. Brassinosteroid mediated signaling genes were also among the candidate genes within two major disease resistance loci (Puccinia psidii resistance), Ppr3 and Ppr5. While brassinosteroids have been tagged as positive regulators in other plant disease resistance interactions, this is the first report in the Eucalyptus – Austropuccinia psidii interaction. Furthermore, several putative resistance genes, underlying known resistance loci and implicated in the interaction have been identified and highlighted for future functional studies. This study provided further insights into the molecular interactions between E. grandis and A. psidii, contributing to our understanding of this pathosystem.